Sistem Pendidikan Finlandia: Membangun Kemandirian dan Semangat Belajar Siswa - Cahyani, Laila Nur (CV. Kurnia Grup, 2023)
The Finnish education system has attracted global attention because it has succeeded in forming students who are independent and enthusiastic about learning. The 20th century philosophy of equality and educational transformation is a key foundation, reflected in a holistic approach to student development. Curriculum transformation and formative evaluation approaches are key instruments in achieving this goal. Qualitative methods and literature studies were used in the research to highlight that Finland's success is not limited to academic achievement alone. More than that, this system succeeds in exploring and advancing students' creativity and adaptation skills. This success is not only local, but also has global relevance. Finland's education model provides inspiration for other countries to improve their education systems. This improvement does not only cover academic aspects, but also involves developing students' creative and adaptive skills. This encourages further research and exchange of experiences between countries, reinforcing the idea that Finland's educational philosophy can be the basis for sustainable educational innovation at an international level. Finland's success paves the way for enriching and enhancing global education, making it a valuable source of inspiration.